Is Your War over Now? Nationalism, Nostalgia, and Japan’s Long Postwar from Gojira (1954) to Godzilla Minus One (2023) - William M. Tsutsui (Humanities)
This essay explores the political dynamics of the Godzilla film franchise over the past 70 years, arguing that critical and scholarly characterizations commonly oversimplify the movies’ complicated messages, which reflect the complex, often contradictory responses of Japanese filmmakers and audiences to the experiences of war, the atomic bombings, defeat, occupation, lasting subordination to the United States, and a seemingly endless postwar period. The analysis focuses on Honda Ishirō’s Gojira (1954), in which pacifist sentiments are tempered by depictions of military weaponry and patriotic pride, and Yamazaki Takashi’s Godzilla Minus One (2023), where ahistorical narratives, misty-eyed nostalgia, and ultranationalist tropes co-exist with strong anti-authoritarian and anti-establishment themes. By contextualizing these two films within the contested history of early postwar Japan and the polarized politics of the early twenty-first century, this essay suggests that the Godzilla series has shown remarkable continuities over time and has captured the profound ambivalence with which the Japanese people have negotiated memory, nationalism, and the charged relationship between Japan and the United States since the end of World War II.